2017
DOI: 10.1038/s41598-017-18075-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Stability during Perturbed Walking in Parkinson’s Disease

Abstract: Gait and balance disorders are major problems that contribute to falls among subjects with Parkinson’s disease (PD). Strengthening the compensatory responses through the use of balance perturbations may improve balance in PD. To date, it is unclear how PD affects the ability to react and adapt to perturbations delivered while walking. This study aims to investigate how PD affects the ability to walk, respond to balance perturbations, and produce acute short-term effects to improve compensatory reactions and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…The study of dynamic balance during overground gait is becoming a field of considerable growing interest because it allows to understand the mechanisms underlying the physiological motor control in healthy subjects, on the one hand, and can be used to identify the strategy adopted by pathological subjects with altered locomotor patterns on the other. [5][6][7] The latter aspect is particularly important in locomotor rehabilitation, where a trade-off between the correction of an altered movement pattern and the maintenance of a safety walking is searched. To fully characterize stability, the CoM motion must be investigated considering not only its absolute displacement in 3D space but also its relative movements with respect to the BoS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of dynamic balance during overground gait is becoming a field of considerable growing interest because it allows to understand the mechanisms underlying the physiological motor control in healthy subjects, on the one hand, and can be used to identify the strategy adopted by pathological subjects with altered locomotor patterns on the other. [5][6][7] The latter aspect is particularly important in locomotor rehabilitation, where a trade-off between the correction of an altered movement pattern and the maintenance of a safety walking is searched. To fully characterize stability, the CoM motion must be investigated considering not only its absolute displacement in 3D space but also its relative movements with respect to the BoS.…”
Section: Introductionmentioning
confidence: 99%
“…4,11 In fact, MoS and FPE have recently been adopted for describing dynamic balance during human gait, both in healthy and pathological subjects. 5,6,[12][13][14] Both of these indices are based on the inverted pendulum model, which is widely used for modeling human gait. 15 Positive values of these indexes indicate that the foot is placed in front of (sagittal plane) or laterally (frontal plane) to the CoM in a stable condition.…”
Section: Introductionmentioning
confidence: 99%
“…With this advantage, MOS has already been widely applied to evaluate gait abnormality and fall risks in a wide range of clinical populations, including patients with stroke [24], Parkinson's Disease [25], hereditary spastic paraparesis [26], as well as CP [9,27]. In a recent prospective observational study, Mehdizadeh et al found that minimum mediolateral MOS was the most important hallmark when assessing the short-term fall risk for patients with dementia [16].…”
Section: Introductionmentioning
confidence: 99%
“…Falls occur when patients attempting to, or actively producing transitional movements (such as sit-to-stand, turning, walking), as the COM tends to be to the outermost boundary of the BOS [5,6]. Axial motor symptoms such as gait and balance impairments are known as L-dopa-resistant and refractory-to-surgery features, as they are associated with progressive lesions of non-dopaminergic sites [7][8][9]. There is growing evidences that physical therapy, and particularly balance exercises, can improve postural stability and reduce fall risk [1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that X com should remain in the BOS, as to satisfy the dynamic stability criterion; hence, the difference between X com and maximum boundary of BOS determined the margin of stability [32]. This approach also became popular in quanti cation and assessment of stability degree in different studies (such as stability during perturbed walking [7], obstacle crossing [33], sit-to-stand task [24], compensatory stepping response after perturbation [34,35]). In this regard, researchers presented novel quantitative terms such as stability degree [21], region of stability [24], limit of stability [6,36], margin of stability (in static [20], or dynamic states [19]), in order to address the extent of stability in healthy subjects or PD patients, considering biomechanical models; however, disregarding control stability theorems.…”
Section: Introductionmentioning
confidence: 99%